The physicochemical characterization and in vivo response of micro/nanoporous bioactive ceramic particulate bone graft materials - Tovar, Nick; Jimbo, Ryo; Witek, Lukasz; Anchieta, Rodolfo [UNESP]; Yoo, Daniel; Manne, Lakshmipradha; Machado, Lucas [UNESP]; Gangolli, Riddhi; Coelho, Paulo G. (Elsevier B.V., 2014)
In this study, the physicochemical characteristics of calcium phosphate based bioactive ceramics of different compositions and blends presenting similar micro/nanoporosity and micrometer scale surface texture were characterized and evaluated in an in vivo model. Prior to the animal experiment, the porosity, surface area, particle size distribution, phase quantification, and dissolution of the materials tested were evaluated. The bone regenerative properties of the materials were evaluated using a rabbit calvaria model. After 2, 4, and 8 weeks, the animals were sacrificed and all samples were subjected to histologic observation and histomorphometric analysis. The material characterization showed that all materials tested presented variation in particle size, porosity and composition with different degrees of HA/TCP/lower stoichiometry phase ratios. Histologically, the calvarial defects presented temporal bone filling suggesting that all material groups were biocompatible and osteoconductive. Among the different materials tested, there were significant differences found in the amount of bone formation as a function of time. At 8 weeks, the micro/nanoporous material presenting similar to 55,TCP:45%,HA composition ratio presented higher amounts of new bone regeneration relative to other blends and a decrease in the amount of soft tissue infiltration. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcium phosphate materials; Porosity; Animal experiment; Histomorphometry